1999
DOI: 10.1111/j.1740-8261.1999.tb00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification and Application of a Pelorus Mark Iii Stereotactic System for Ct‐guided Brain Biopsy in 50 Dogs

Abstract: The Pelorus Mark III Stereotactic System is a commercially available device for CT-guided stereotactic brain biopsy in people. With relatively minor modifications, this device was used to safely and accurately perform CT-guided stereotactic brain biopsies in 50 dogs with intracranial lesions. Modifications were necessary to accommodate a 90 degree shift in orientation of the canine head compared to the human head during the imaging phase of the procedure, and to facilitate other phases of the biopsy procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 9 publications
4
70
0
2
Order By: Relevance
“…Free‐hand, image‐guided, and endoscope‐assisted brain biopsy has been described for dogs84, 85, 86; however, stereotactic‐guided procedures have many advantages. Both CT‐ and MRI‐based stereotactic systems were developed for dogs in the 1980s in the experimental setting,87, 88 and a variety of stereotactic approaches to clinical brain biopsy have been described in dogs and cats, the majority of which have involved CT‐based systems 89, 90, 91, 92, 93, 94, 95. Only 1 commercially available MRI‐based system has been reported,96 that is likely to become a mainstay of stereotactic biopsy in the future.…”
Section: Brain Biopsymentioning
confidence: 99%
“…Free‐hand, image‐guided, and endoscope‐assisted brain biopsy has been described for dogs84, 85, 86; however, stereotactic‐guided procedures have many advantages. Both CT‐ and MRI‐based stereotactic systems were developed for dogs in the 1980s in the experimental setting,87, 88 and a variety of stereotactic approaches to clinical brain biopsy have been described in dogs and cats, the majority of which have involved CT‐based systems 89, 90, 91, 92, 93, 94, 95. Only 1 commercially available MRI‐based system has been reported,96 that is likely to become a mainstay of stereotactic biopsy in the future.…”
Section: Brain Biopsymentioning
confidence: 99%
“…Tissue samples were obtained from the lesions either by a CT-guided stereotactic brain biopsy procedure using a modified human Pelorus Mark III apparatus (n ϭ 44) or intraoperatively at craniotomy (n ϭ 49). 13 All smear preparations were made following procedures as previously described for humans. 1,15 Briefly, small tissue pieces (Ͻ0.5 ϫ 0.5 ϫ 0.5 mm) were harvested from both ends of a 3 ϫ 1.8-mm biopsy needle tissue core sample.…”
Section: Methodsmentioning
confidence: 99%
“…However, using air-dried smears obtained from either impression or needle aspiration, the cytological characteristics of two canine meningiomas and a glioma have been described. 2,8,18 With our recent development of a modified human CTguided stereotactic biopsy system for intracranial lesions in dogs and cats 12,13 and our need for a precise clinical diagnosis for planning either conventional or experimental therapeutic approaches, we have begun evaluation of some feline and canine primary nervous system tumors using this smear technique.…”
mentioning
confidence: 99%
“…In that report, there was agreement between stereotactic biopsy and open biopsy or necropsy in 20 of 22 cases (91%). 36 Adverse events associated with biopsy were recorded in 5 of 41 animals (12%), with 3 animals (7%) requiring euthanasia. 36 In a smaller report, adverse events associated with stereotactic biopsy were described in 6 of 23 dogs (27%), with mortality occurring in 2 of 23 dogs (8%); diagnostic accuracy could not be determined.…”
Section: Stereotactic Brain Biopsymentioning
confidence: 99%
“…The Kopf system was recently utilized in small dogs and found to correspond to selected supratentorial targets within 0.9 + 0.9 mm. 78 An adaptation of the Pelorus III device 36 was accurate to 3.5 + 1.6 mm, and a manufactured device described by Moissonnier et al 53 had a reported accuracy of 2.9 + 1.0 mm. Despite numerous reports on the validation of frame-based systems in canine cadavers, there is only one large study 36 describing clinical findings from neurologically affected dogs.…”
Section: Stereotactic Brain Biopsymentioning
confidence: 99%